INFLUENCE OF ATMOSPHERIC AIR POLLUTION IN THE PROCESS OF MINING AND TECHNICAL COMPANY ACTIVITIES ON THE HEALTH OF THE POPULATION OF AN INDUSTRIAL CITY - Вера Викторовна Кислицына; Дмитрий Вячеславович Суржиков; Юлия Сергеевна Ликонцева (Медицина в Кузбассе)
The study aim was an assessment of the risk of damage to the health of the population of an industrial city due to air pollution by atmospheric emissions from a mining and technical company. Materials and methods. The volume of maximum permissible emissions of a mining and technical company was used in the work. The assessment of the distribution and impact of atmospheric emissions was carried out at 30 calculated points selected on the basis of a map of the city of Novokuznetsk, the Kemerovo Region. The maximum and average annual concentrations of pollutants were calculated. The risk values of chronic intoxication and carcinogenic risk, hazard coefficients and indices were determined. The obtained risk values were compared with acceptable levels. Risk values were determined taking into account the background concentrations of substances. Results. Exceeding the maximum and average annual concentrations of pollutants was not detected at all impact points. The total risk levels of chronic intoxication ranged from 0.00004 to 0.001, not exceeding the acceptable level (0.02). The highest value of the total level of risk of chronic intoxication (0.001) was found in the micro-district located closer to the sources of exposure. The main contribution to the formation of the risk level was made by inorganic dust with a content of SiO2 < 20 %, nitrogen dioxide and sulfur dioxide. The total risk levels of chronic intoxication, taking into account background exposure to pollutants, were in the range from 0.052 to 0.073, significantly exceeding the acceptable level. The largest specific weight of pollutants in the risk of chronic intoxication, taking into account the background, was observed in nitrogen dioxide and carbon monoxide. The hazard indices for chronic inhalation exposures for all substances, taking into account the background, exceeded one, therefore, there was the impact on the body. The calculated levels of carcinogenic risk did not exceed the acceptable level, both without taking into account the background impact of pollutants, and with regards to the background. Conclusion. Mining and technical company activities make a certain contribution to air pollution in Novokuznetsk, without causing significant damage to public health. High risk levels of chronic intoxication and hazard indices, calculated taking into account the background exposure to pollutants, are due to the general unfavorable situation in the city.